1991
DOI: 10.1002/ajh.2830370405
|View full text |Cite
|
Sign up to set email alerts
|

Agranlocytosis caused by ticlopindine and its mechanism

Abstract: A 75-year-old female patient with agranulocytosis caused by ticlopidine is reported. She took the drug at 200 mg/day for 30 days to prevent recurrence of cerebral infarction. The leukocyte count at the nadir was 500/microliters on the 34th day since she started to take the drug. Complete recovery of her peripheral leukocytes came 12 days after its withdrawal. In this patient, mechanisms of ticlopidine-caused agranulocytosis were studied. The lymphocyte stimulation test using ticlopidine was negative. In the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 5 publications
1
32
0
Order By: Relevance
“…These observations indicate that the formation of reactive intermediates followed by conjugation with GSH is the major metabolic route of ticlopidine in rats. Ticlopidine has been reported to induce agranulocytosis (Ono et al, 1991), thrombotic thrombocytopenic purpura (Muszkat et al, 1998;Steinhubl et al, 1999), aplastic anemia (Mataix et al, 1992), and hepatotoxicity (Takikawa, 2005). Immune reactions seem to be involved in at least some serious adverse events, such as agranulocytosis (Ono et al, 1991) and hepatic injury (van Zanten and McCormick, 1996;Tsai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that the formation of reactive intermediates followed by conjugation with GSH is the major metabolic route of ticlopidine in rats. Ticlopidine has been reported to induce agranulocytosis (Ono et al, 1991), thrombotic thrombocytopenic purpura (Muszkat et al, 1998;Steinhubl et al, 1999), aplastic anemia (Mataix et al, 1992), and hepatotoxicity (Takikawa, 2005). Immune reactions seem to be involved in at least some serious adverse events, such as agranulocytosis (Ono et al, 1991) and hepatic injury (van Zanten and McCormick, 1996;Tsai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits adenosine 59-diphosphate (ADP)-induced platelet aggregation by irreversible binding of an active thiol metabolite to the 2-methylthio-ADP-binding receptor. Although it is effective in preventing atherothrombotic events in cardiovascular, cerebrovascular, and peripheral vascular disease, administration of ticlopidine results in a relatively high incidence of hematologic toxicities (Lesesve et al, 1994;Love et al, 1998) such as agranulocytosis (Ono et al, 1991), thrombotic thrombocytopenic purpura (Steinhubl et al, 1999), and aplastic anemia (Mataix et al, 1992). Therefore, clopidogrel, a second-generation thienopyridine antiplatelet agent is a safer, better-tolerated alternative to ticlopidine.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits ADP-induced platelet aggregation by a mechanism that appears to involve effects on the 2-methylthio-ADP-binding receptor. Although effective in preventing atherothrombotic events in cardiovascular, cerebrovascular, and peripheral vascular disease, administration of ticlopidine results in a relatively high incidence of hematological toxicities (Lesesve et al, 1994;Love et al, 1998) such as agranulocytosis (Ono et al, 1991), thrombotic thrombocytopenic purpura (Muzkat et al, 1998;Steinhubl et al, 1999), and aplastic anemia (Mataix et al, 1992;Ferrer et al, 1998). Recently, reports of ticlopidine-induced hepatotoxicity have also appeared (Grieco et al, 1998;Perez-Balsa et al, 1998;Zeolla and Carson, 1999).…”
mentioning
confidence: 99%
“…The mechanisms of hematological toxicity and hepatotoxicities caused by ticlopidine are unclear. However, it has been suggested that ticlopidine-induced agranulocytosis is caused either by direct cytotoxicity or via an immune-mediated reaction (Ono et al, 1991). Liu and Uetrecht (2000) have recently shown the involvement of a myeloperoxidase/H 2 O 2 /Cl Ϫ system and activated neutrophils in the metabolism of ticlopidine to a reactive intermediate, thiophene-S-chloride.…”
mentioning
confidence: 99%